The importance and prognostic effect of thyroid hormones in patients with transposition of the great arteries - Arslanoğlu, Ergin; Kara, Kenan Abdurrahman; Bakhshaliyev, Shiraslan; Yiğit, Fatih; Tanrıverdi, Doğan Çağrı; Tunçer, Eylem; Çine, Nihat; Ceyran, Hakan (The European Research Journal, 2024)
Objectives: Transposition of the great arteries (TGA) is a rare congenital heart disease that occurs in 3 in 10,000 newborns and is rapidly fatal (90%) within one year if left untreated. The prognosis of this pathology changed after introducing an early arterial switch operation (ASO), while the left ventricle could still adapt to systemic high-pressure conditions. Appropriate regulation of thyroid hormones positively impacts metabolism, cardiac function, and postoperative recovery. Therefore, regular thyroid hormone monitoring and thyroid function monitoring of TGA patients may help to improve the health status and prognosis of this group of postoperative patients. Methods: In our study, 127 patients who underwent ASO at our pediatric cardiac surgery clinic between 01.01.2014 and 18.09.2021 were retrospectively analyzed and included. Among the patients, 43% (n=54) were females, and 57% (n=73) were males. Results: The coronary arteries were normal in 89.7% (n=114) and abnormal in 10.3% (n=13) of the patients. Twenty-one of the patients exited, and mortality was calculated to be 16.5%. There were no significant differences in mortality or thyroid stimulating hormone (TSH), free thyroxine (T4), or free triiodothyronine (T3) values (P=0.674, P=0.345, P=0.478). In our study, in which we investigated the effect of thyroid hormone levels on prognosis in neonatal patients with TGA with normal free T3, T4, and TSH values, we found that TSH levels were greater in the group with advanced aortic regurgitation and exitus, although the effect of thyroid hormones on postoperative results was not statistically significant. Conclusions: Congenital hypothyroidism is a common disease with cardiac effects. During the neonatal period, this disease may conceal itself. Careful, expert clinical follow-up and clinical trials are crucial to improve outcomes in the surgical treatment of transposition of the great arteries, a complex congenital heart disease.